2008
DOI: 10.1053/j.gastro.2008.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Microvascular Blood Detection From the Endoscopically Normal Colonic Mucosa: Biomarker for Neoplasia Risk

Abstract: Background & Aims-We have previously utilized a novel biomedical optics technology, fourdimensional elastically-scattered light fingerprinting, to demonstrate that in experimental colon carcinogenesis, the predysplastic epithelial microvascular blood content is markedly elevated. In order to assess the potential clinical translatability of this putative field effect marker, we characterized the early increase in blood supply (EIBS) in humans in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 30 publications
3
56
1
Order By: Relevance
“…[6][7][8][9][10] These techniques are able to provide information regarding the tissue substructure, which can serve as biomarkers for the presence of intraepithelial neoplasia. Recently, Backman and Roy have proposed measurement of the field effect of colon carcinogenesis using light scattering techniques as a means of risk stratification and prescreening for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] These techniques are able to provide information regarding the tissue substructure, which can serve as biomarkers for the presence of intraepithelial neoplasia. Recently, Backman and Roy have proposed measurement of the field effect of colon carcinogenesis using light scattering techniques as a means of risk stratification and prescreening for CRC.…”
Section: Introductionmentioning
confidence: 99%
“…A field effect has been noted in light-scattering spectroscopy of the colon. 54 As the number of dysplastic ovaries in this study was small, however, a firm conclusion cannot be drawn.…”
Section: Discussionmentioning
confidence: 75%
“…Hemoglobin concentration measured from this depth was diagnostic for early detection of colonic neoplasia. 2 For simplicity, we will maintain the same optical properties as the first case study since the optical properties of the colon have been found to be similar. 49 In general, the optical properties will need to be adjusted based on the tissue or organ being investigated.…”
Section: Case Studiesmentioning
confidence: 99%
“…Our optical and histological investigations in human patients and animal models of colon carcinogenesis have shown diagnostic alterations in hemoglobin concentration that are present in the mucosa but attenuated at deeper submucosal depths. [1][2][3][4][5] Studies with angle-resolved low-coherence interferometry demonstrate that elevation of nuclear diameter associated with dysplasia in Barrett's esophagus was only detectable at a depth of 200 to 300 μm and not observable at 0 to 100 μm or 100 to 200 μm. 6 Several fiber-optic probe modalities have been developed to target the mucosal layer with a wide field of view.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation